Career aspirations of R&D professionals in Malaysian organizations - Ismail, Maimunah; Ramly, Efizah Sofiah; Mohd Rasdi, Roziah (2008)
R&D professionals play vital roles in work organizations, society and nation building in today’s scenario of development. Since research on R&D professionals’ career aspirations is context specific, there is yet limited empirical investigation on their career life in relations to career aspirations particularly based on Malaysian scenario. Specifically, this study aims to examine the relationship between self-efficacy, organizational socialization, and continuous improvement practices with career aspiration among R&D professionals. The framework of this study is based on Schein’s Career Anchor Theory and Social Cognitive Career Theory (SCCT). The former describes the components that make up career aspirations, while the latter explains the interaction of cognitive-person variables (e.g. self-efficacy), external environment factors (e.g. organizational socialization) and behavior (e.g. continuous improvement practices) with career aspirations. This study presents results based on pre-testing data involving 49 R&D professionals from two public organizations and four Multinational Corporations (MNCs) in Malaysia through a survey research design. The data were analysed using descriptive statistics and Pearson Product-Moment correlation. The results indicate that the three selected factors, namely, self-efficacy, organizational socialization and continuous improvement practices, show significant positive relationships with the respondents’ career aspirations. The study concludes that the variables seem to have the predictive potential to career aspiration of R&D professionals.